Actinocin derivative interaction with DNA molecules at different concentrations of monovalent alkaline metals ions Na+ and K+ - Minakova, Е. А.; Kruglova, Е. B. (Biophysical Bulletin, 2009)
Spectrophotometric titration method is used to study the actinomycin derivative ActII*, an analog of theactinomycin D, interaction with calf thymus DNA. Models of several types of complexes forming betweenligand and polynucleotide matrix are considered. DALSMOD optimization program of spectrophotometricconcentration dependencies are used to choose the optimal complexation model. The results of the calculation are evidence of the three different spectral types of complexes in the system Act II* -DNA. Na+and K+ions are considered as competitors of the ligand by one of the binding sites. Logarithms of binding constants of each type of complexes depend linearly on the logarithm of NaCl and KCl concentrations in the considered interval. The slopes of these dependencies are different for Na+and K+ions.